2010
DOI: 10.1016/j.marpetgeo.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The physics of gas chimney and pockmark formation, with implications for assessment of seafloor hazards and gas sequestration

Abstract: a b s t r a c tPockmarks form where fluids discharge through seafloor sediments rapidly enough to make them quick, and are common where gas is present in near-seafloor sediments. This paper investigates how gas might lead to pockmark formation. The process is envisioned as follows: a capillary seal traps gas beneath a fine-grained sediment layer or layers, perhaps layers whose pores have been reduced in size by hydrate crystallization. Gas accumulates until its pressure is sufficient for gas to invade the seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 34 publications
13
175
0
8
Order By: Relevance
“…5). Other indications of gas in sediments, such as acoustically disrupted columns, or "chimneys" (sensu Cathles et al, 2010), were not observed in any of the estuaries.…”
Section: Natural Gas (Ng)mentioning
confidence: 84%
“…5). Other indications of gas in sediments, such as acoustically disrupted columns, or "chimneys" (sensu Cathles et al, 2010), were not observed in any of the estuaries.…”
Section: Natural Gas (Ng)mentioning
confidence: 84%
“…The failure of the capillary pressure was suggested as the main cause for the formation of the pockmarks. Seal fails when buoyancy pressure exceeds the capillary pressure during hydrate crystallization and gas accumulations, which leads to the formation of large escape of gases to the seafloor initiating dissolution of the surrounding sediment by ocean water and forms pockmarks (Cathles et al, 2010). The linear arrangement of pockmarks indicates their association with fault zones (Haskell et al, 1999).…”
Section: Pockmarksmentioning
confidence: 99%
“…A model by Woolsey et al (1975) simulating "diatreme emplacements by 57 fluidization" supports this theory. Recently, Cathles et al (2010) came up with a 58 conceptual model of pockmark and gas chimney formation. They assume that there 59 is a capillary seal which traps the gas in the deeper sediment.…”
Section: But Many Published Examples Indicate Formation 38mentioning
confidence: 99%